A pathogenic variant in the transforming growth factor beta I (TGFBI) in four Iranian extended families segregating granular corneal dystrophy type II: A literature review - Mohammadi, Aliasgar (Iran J Basic Med Sci, 2020)
OBJECTIVE(S): Granular and lattice corneal dystrophies (GCDs & LCDs) are autosomal dominant inherited disorders of the cornea. Due to genetic heterogeneity and large genes, unraveling the mutation is challenging. MATERIALS AND METHODS: Patients underwent comprehensive clinical examination, and targeted next-generation sequencing (NGS) was used for mutation detection. Co-segregation and in silico analysis was accomplished. RESULTS: Patients suffered from GCD. NGS disclosed a known pathogenic variant, c.371G>A (p.R124H), in exon 4 of TGFBI. The variant co-segregated with the phenotype in the family. Homozygous patients manifested with more severe phenotypes. Variable expressivity was observed among heterozygous patients. CONCLUSION: The results, in accordance with previous studies, indicate that the c.371G>A in TGFBI is associated with GCD. Some phenotypic variations are related to factors such as modifier genes, reduced penetrance and environmental effects.